2014
DOI: 10.1186/s40359-014-0049-9
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver stress in stroke survivor: data from a tertiary care hospital -a cross sectional survey

Abstract: BackgroundA principal caregiver (CG) is directly affected by patient’s health problems that lead to CG strain. Pakistan has an estimated 4.8% of the population suffering from strokes. The study objective was to evaluate the caregiver level of stress and the factors which make CGs more prone to stress and also to identify the predictive role of factors such as age, sex, educational, marital status on their burden.MethodsThis was a cross-sectional survey. 112 Participants were chosen on the basis of being direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…This may lead to the neglect of the needs of the other family members. 11 In the current study, the mean CSI score among the nuclear family was 11.38±1.48 when compared to 11.24±0.93 among the non nuclear family. However, this difference was not found to be statistically significant (P=0.407).…”
mentioning
confidence: 42%
“…This may lead to the neglect of the needs of the other family members. 11 In the current study, the mean CSI score among the nuclear family was 11.38±1.48 when compared to 11.24±0.93 among the non nuclear family. However, this difference was not found to be statistically significant (P=0.407).…”
mentioning
confidence: 42%
“…Each caregiver's burden was mostly related to their age (mean age = 55.97), depressed affect, somatic complaints, number of caregiving hours (>8 hr per day) and stroke survivors’ functional capacity. Caregivers’ age and hours of caregiving between 6–12 hr were also found to contribute to caregivers’ burden in a study of stroke caregivers conducted in South Africa (Gbiri, Olawale, & Isaac, ) and Pakistan (Ain, Dar, Ahmad, Munzar, & Yousafzai, ). This result concurred with the study in Hong Kong which showed that Chinese caregivers’ physical conditions directly affected caregivers’ burden (Lau et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported on the burden of family caregivers and chronic diseases such as stroke, dementia, and cancer [7][8][9][10]. Family caregivers of patients with cancer report high levels of depression, often higher than their care recipients [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have been conducted to evaluate the burden of caregivers in severe conditions, such as cancer, dementia, or stroke, demonstrating high levels of burden and psychosocial distress in these populations [7][8][9][10]. However, the burden of family members of RA patients has not been previously evaluated.…”
Section: Introductionmentioning
confidence: 99%